RELATIONSHIP AMONG ADIPOSITY INDEXES IN WOMAN AGED BETWEEN 30 AND 34 YEARS OLD (Fiep Bulletin - online, 2014)
Objective: To analyze the relationship between adiposity indexes in a female population. Methods: The sample was composed by 297 women aged between 30 and 34 years old and they were visitors of the coast of Parana State. Body density was calculated by the predictive equation of JACKSON & POLLOCK (1978) with three skinfolds and fat percentage by the equation of SIRI (1961). BMI was classified by reference of WHO (1997) and waist perimeter with standardization suggested by HEYWARD and STOLARCZYK (1996). For data treatment   descriptive statistic was used; One-Way Anova and the post-hoc of Tukey among BMI groups, Pearson bivariate two-tailed correlation among adiposity indexes, (p = 0.05); and multiple regression analisys with BMI as dependent variable and fat percentage, lean body mass and age as independent variables. Results: The higher the average value of BMI was, the higher systolic resting blood pressure, body mass, waist perimeter, ? of triceps, suprailiac and abdominal skinfolds, fat percentage, fat mass and lean body mass were, and all these variables were different among BMI groups (p
Keywords: Indexes; adiposity; women